3 of anything positive is greater than 2 of the same thing.
I can't think of an exception.
Answer:
y+3=-11/7(x-2)
Step-by-step explanation:
y-y1=m(x-x1)
m=(y2-y1)/(x2-x1)
m=(8-(-3))/(-5-2)
m=(8+3)/(-7)
m=11/-7
m=-11/7
y-(-3)=-11/7(x-2)
y+3=-11/7(x-2)
Answer:
10
Step-by-step explanation:
Answer:
The solutions are x = -7, 6.
Step-by-step explanation:
To find the solutions, move everything to one side of the equation so the equation is equal to 0. Then factor. Set the factors equal to 0 and solve for x.
![x^2 + x - 30 = 12\\x^2 + x -42=0\\(x+7)(x-6) = 0](https://tex.z-dn.net/?f=x%5E2%20%2B%20x%20-%2030%20%3D%2012%5C%5Cx%5E2%20%2B%20x%20-42%3D0%5C%5C%28x%2B7%29%28x-6%29%20%3D%200)
x+7 = 0
x = -7
and
x-6 = 0
x = 6
The solutions are x = -7, 6.
A. you have to do the whole 30/2 i just had this on a test. GOOD LUCK